WAJAH TRANSPORTASI PERKOTAAN PADA KOTA - KOTA MENUJU KOTA METROPOLITAN (STUDI KASUS: SEMARANG METROPOLITAN) - Ismiyati Ismiyati; Sugiono Soetomo (Universitas Bandar Lampung, 2017)
This study will describe influence of growth of urban uncontrollably toward outside or which is often referred as by urban sprawl to moda choce. Growth of town into metropolitan area need careful because besides affecting social segregasi also cause not effisient mobility of suburban , because journey become long distance is resident activity still concentration at downtown (core city ) and also the happening of integration of each town also will complicate arrangement of urban transportation system Purpose of this research is to identify factors growth of urban uncontrollably toward outside its influence urban sprawl to moda choce with a view to recommend handling of problems of transportation at metropolitan area. Approach method with approach of spasial pursuant to understanding of human being interaction with urban environment that is by studying dynamics friction of resident in taking choice suburban residence and its mobility choice that is choice of moda transportation. Method acquirement of data by using technique method interview household by random proposional pursuant to strata of sosio-ekonomi at region of suburban. Technique analyse by using analysis of crosstabulation statistic with test of significan to describe factors influencing growth of urban and its influence to moda choice. Result of from this research describe that growth of town toward town boundary of Semarang unegual and its surroundings its speed at some district exist in study region. As for factors influencing growth of town besides aksessibilitas there is social factor in the form of change of life style toward requirement of settlement with balmy environment and requirement of transportation. Result of from this study is] expected useful for the day- dream of problems of urban transportation by integrating between operation of policy of settlement of settlement environment and policy of operation of transportation system at natural towns of metropolitan area.